2018
DOI: 10.1109/tpel.2017.2723638
|View full text |Cite
|
Sign up to set email alerts
|

Variable Structure Control in Natural Frame for Three-Phase Grid-Connected Inverters With LCL Filter

Abstract: Abstract-This paper presents a variable structure control in natural frame for a three-phase gird-connected voltage source inverter with LCL filter. The proposed control method is based on modifying the converter model in natural reference frame, preserving the low frequency state space variables dynamics. Using this model in a Kalman filter, the system state-space variables are estimated allowing to design three independent current sliding-mode controllers. The main closed-loop features of the proposed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…9 the impact of deviations of ±30% on the rated values of filter inductance were analyzed. Similar tests for variation of the converter output filter parameters have been performed in [45] for sliding mode control algorithm with Kalman filter, in [41] for a combination of robust control, state estimator, and linear matrix inequality (LMI) optimizations, and in [46] for a linear single current loop control with hybrid damper. As it can be seen from obtained results the overestimation and underestimation of the filter values didn't significantly effect the steady state performance of the converter which proves that the resistance to parameter variations is comparable to [41], [45], [46].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 the impact of deviations of ±30% on the rated values of filter inductance were analyzed. Similar tests for variation of the converter output filter parameters have been performed in [45] for sliding mode control algorithm with Kalman filter, in [41] for a combination of robust control, state estimator, and linear matrix inequality (LMI) optimizations, and in [46] for a linear single current loop control with hybrid damper. As it can be seen from obtained results the overestimation and underestimation of the filter values didn't significantly effect the steady state performance of the converter which proves that the resistance to parameter variations is comparable to [41], [45], [46].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Similar tests for variation of the converter output filter parameters have been performed in [45] for sliding mode control algorithm with Kalman filter, in [41] for a combination of robust control, state estimator, and linear matrix inequality (LMI) optimizations, and in [46] for a linear single current loop control with hybrid damper. As it can be seen from obtained results the overestimation and underestimation of the filter values didn't significantly effect the steady state performance of the converter which proves that the resistance to parameter variations is comparable to [41], [45], [46]. For a more detailed experimental study on parameter variation effects for FCS-MPC operated converters for UPS the reader is refereed to [7] where it is demonstrated that stability is not lost even under heavy mismatch between the model parameters used by the algorithm and those in the experimental set-up.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A hybrid steering logic was presented in the work of [3], analysis and simulations are presented to demonstrate the performance of the hybrid steering logic in the work of [4]. A variable structure control in natural frame for a three-phase girdconnected voltage-source inverter with LCL filter was presented in [5].The proposed control method is based on modifying the converter model in natural reference frame, preserving the low-frequency state-space variables dynamics. Some problems about the attitude maneuver control are discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate digital control applications, the sliding mode observer is studied in the discrete-time field. Pole placement technique [18,19] is used to design the switching surface; desired dynamic characteristics can be achieved through eigenvalue placement. To force the state trajectories reach and subsequently remain on the eventual sliding surface with a good movement quality, free hierarchical law is adopted as switching scheme, and discretized reaching law [20] is used to design the quasi-sliding mode and reaching process.…”
Section: Introductionmentioning
confidence: 99%